PENDIDIKAN INTEGRATIF DALAM PEMBELAJARAN FIQIH DI MTsN 2 BUKITTINGGI - Wirman Hanizon (El-Rusyd, 2019)
Integrative Approach in Learning Fiqh in MTs Negeri 2 Bukittinggi, aims to examine the extent to which the implementation of Integrative Approach in Learning Fiqih in MTs Negeri 2 Bukittinggi, which includes: First, how the preparation of teachers, students, and media in learning jurisprudence with using an integrative approach. Second, how is the process of applying integrative approach in learning fiqih.Third, how the evaluation done by the teacher in learning.The research approach chosen is qualitative approach. The characteristic of this approach lies in its purpose to describe a case by understanding meaning and phenomenon. While the data collection through interview method, observation and documentation. The effort to implement integrative approach in learning Fiqh in MTs Negeri 2 Bukittinggi is reflected from the data.The result of this research shows that the implementation of integrative approach has good or maximal result in the formation of students who are competent in worship, the mastery of the jurisprudence material in terms of theory (cognitive), understanding (affective) , and practice (psychomotor). The gap between theory, pemahan, and practice can be overcome. Students are not only good at memorizing theories about thaharah, wudu ', and prayer but students are also able to practice it properly and correctly in everyday life.